USING ELECTRONIC PLATFORMS IN INCLUSIVE EDUCATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Informatics and information technologies, computer literacy, and knowledge of digitalization are becoming increasingly important in modern society. Improving the methods of teaching informatics and information technologies in secondary schools is a very important factor in preparing students for the digital future. Various interactive teaching methods and innovative educational platforms can play an important role in this process. Nowadays, informatics and information technologies are becoming an important part of modern education. As a result, traditional teaching methods cannot fully meet the needs of today's students, because today's younger generation is growing up with various gadgets and devices. It is a little more difficult to impress them with simple things.